Short Physical Performance Battery and all-cause mortality: systematic review and meta-analysis - Pavasini R; Guralnik J; Brown JC; di Bari M; Cesari M; Landi F; Vaes B; Legrand D; Verghese J; Wang CL; Stenholm S; Ferrucci L; et al. (BIOMED CENTRAL LTD, 2025)
Background: The Short Physical Performance Battery (SPPB) is a well-established tool to assess lower extremity physical performance status. Its predictive ability for all-cause mortality has been sparsely reported, but with conflicting results in different subsets of participants. The aim of this study was to perform a meta-analysis investigating the relationship between SPPB score and all-cause mortality.Methods: Articles were searched in MEDLINE, the Cochrane Library, Google Scholar, and BioMed Central between July and September 2015 and updated in January 2016. Inclusion criteria were observational studies; > 50 participants; stratification of population according to SPPB value; data on all-cause mortality; English language publications. Twenty-four articles were selected from available evidence. Data of interest (i.e., clinical characteristics, information after stratification of the sample into four SPPB groups [0-3, 4-6, 7-9, 10-12]) were retrieved from the articles and/or obtained by the study authors. The odds ratio (OR) and/or hazard ratio (HR) was obtained for all-cause mortality according to SPPB category (with SPPB scores 10-12 considered as reference) with adjustment for age, sex, and body mass index.Results: Standardized data were obtained for 17 studies (n = 16,534, mean age 76 +/- 3 years). As compared to SPPB scores 10-12, values of 0-3 (OR 3.25, 95% CI 2.86-3.79), 4-6 (OR 2.14, 95% CI 1.92-2.39), and 7-9 (OR 1.50, 95% CI 1. 32-1.71) were each associated with an increased risk of all-cause mortality. The association between poor performance on SPPB and all-cause mortality remained highly consistent independent of follow-up length, subsets of participants, geographic area, and age of the population. Random effects meta-regression showed that OR for all-cause mortality with SPPB values 7-9 was higher in the younger population, diabetics, and men.Conclusions: An SPPB score lower than 10 is predictive of all-cause mortality. The systematic implementation of the SPPB in clinical practice settings may provide useful prognostic information about the risk of all-cause mortality. Moreover, the SPPB could be used as a surrogate endpoint of all-cause mortality in trials needing to quantify benefit and health improvements of specific treatments or rehabilitation programs.